Patient perceptions of healthy weight promotion in dental settings. Issue 1 (July 2019) - Wijey, T.; Blizard, B.; Louca, C.; Leung, A.; Suvan, J.
Abstract: Introduction: Excess weight is a risk factor for systemic and oral diseases. Since dental professionals are already involved in imparting overall health messages when certain conditions impact oral health, it should make sense that they also deliver related health messages such as promoting the maintenance of healthy weight for patients. Objectives: This study evaluated the perceptions of adult patients attending private dental clinics on healthy weight promotion by dental professionals. Methods: A cross-sectional multicenter survey was designed and set in four private dental clinics (London/Hampshire) between April and July 2015. All eligible patients (≥ 18 years) completed a questionnaire. Body Mass Index (BMI; kg/m 2 ) was calculated from height and weight measurements. Questionnaire content was centred on patient perceptions of 6 domains with the primary domain as to whether patients would accept healthy weight promotion by dental professionals. Results: 213 adults (aged 20–85 years) participated in this study and 58.2% were females. Although the overwhelming majority endorsed healthy weight promotion by the dental team, the overweight/obese were significantly more sensitive (BMI screening χ2 trend = 6.840, p = 0.009; healthy weight information χ2 trend = 6.231, p = 0.013). Awareness of risk of periodontitis, carcinoma and overall adverse health outcomes associated with overweight or obesity was low. Conclusion: The study cohort was well primed for healthy weight advice. Routine healthy weight promotion and BMI screening should be considered in the private dental clinic settings. Clinical significance: This is an opportunity to collaborate with other health care professionals to support overall health monitoring/advice; a common risk factor strategy as recommended by the WHO. Future research is merited for this new initiative particularly perceptions of: dental teams' on healthy weight management, longitudinal interventions, NHS, children/parents and separate obese groups.